Effect of different additives on ash fusion characteristic and mineral phase transformation of iron-rich Zhundong coal. (1st January 2022) - Wang, Yibin; Li, Liangyu; An, Qiwei; Tan, Houzhang; Li, Peng; Peng, Jianghua
Highlights: Six types of additives influencing ash fusion temperatures of ZD coal were studied. An optimal additive composed of alumina-rich ash, MgO and dolomite was proposed. Formation of Mg-Fe-Al oxides delays the dissolving of Fe/Mg oxide into silicates. Abstract: Fundamental research on the mineral transformation of iron-rich coal is very necessary for extending its utilization at elevated temperature. In this work twelve runs with six types of additives (halloysite, alumina-rich ash, dolomite, SiO2, CaO and MgO) at different mixing proportions were sorted, to adjust the relative content of Si, Al, Ca or Mg element in coal ashes targeting to improve the slagging characteristic. Ash fusion tests and the preparation of coal ashes at elevated temperatures (1100, 1150 and 1250℃) were performed, respectively. The effects of additive type and blending ratio on the fusion characteristic and the mineral phase transformation were explored. Elemental composition, crystalline mineral phases and micro-morphologies of coal ashes were characterized via various technical approaches. The results showed that 3% alumina-rich ash or dolomite significantly improve the deformation temperature of iron-rich coal. While the addition of halloysite or SiO2 with a same proportion sharply decreases the softening and flow temperatures of coal ash, except for slightly increasing the deformation temperature. The composite additive consisting of alumina-rich ash, MgO and dolomite, could promote the formation of MgFe2 O4, FeAl2 O4, Mg(Fe, Al)2 O4 or MgAl2 O4 which inhibit the melting of coal ash. However, a low proportion of Si-rich additive into iron-rich coal is not suggested.